Penilaian Pembelajaran Sejarah Konstruktivistik: Pendekatan Critical Discourse Analysis - Nur Fatah Abidin; Hermanu Joebagio; Sariyatun Sariyatun (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2017)
This article discusses about assessment of the constructivism approach in history learning with Critical Discourse Analysis (CDA). CDA provides a set of in-depth analysis method which includes the realm of linguistic, social, and cultural. The CDA is composed of three stages of a dynamic analysis and related to each other: (1) analysis of the text, (2) analysis of the practice of discourse, and (3) analysis of social practices. In the context of history learning with constructivism approach, the third stages can be used to assess the development of the system and the structure of the thinking of learners. CDA approach can be used to analyse the work of learners with description test. Therefore, the necessary rubric based on assessment rubrics and discourse analysis of the level of development of thinking learners. Based on the research results, the CDA can be used in learning history, specifically with constructivism approach. Assessment of history learning with constructivism approach is expected to be an alternative assessment of learning that not only assess student knowledge of quantity, but also to measure the development of the system and the structure of the thinking of learners.